Upaya Memotivasi Semangat Belajar Siswa Melalui Model Pembelajaran Integreted Reading and Composition Pada Pelajaran Bahasa Indonesia - Yetti, Yetti (JURNAL GLOBAL EDUKASI, 2017)
Abstract: The purpose of this study is to increase the motivation of students' learning spirit through integrated learning and composition learning model in Indonesian Language lesson. Subjects in this study were the seventh grade students of SMP Negeri 1 Aek Kuasan kab. Asahan which amounts to 37 students. From the results of the assessment on the learning activities of students cycle I is 62% increase to 86% in cycle II students actively follow the learning efforts to motivate the spirit of student learning in reading and writing quickly through the learning model Integreted Reading and Composition on Indonesian lessons. It can be concluded that through integrated learning and composition learning model can increase the motivation of students' learning spirit in reading and writing fast in Indonesian lesson. Keywords: integrated reading and composition, reading, writing Abstrak: Tujuan penelitian ini adalah untuk peningkatan motivasi semangat belajar siswa melalui model pembelajaran integrated reading and composition pada pelajaran Bahasa Indonesia. Subjek dalam penelitian ini adalah siswa kelas VII SMP Negeri 1 Aek Kuasan kab. Asahan yang berjumlah 37 siswa. Dari hasil penilaian pada aktivitas belajar siswa siklus I terdapat 62% meningkatkan menjadi 86% pada siklus II siswa aktif mengikuti pembelajaran upaya memotivasi semangat belajar siswa dalam membaca dan menulis cepat melalui model pembelajaran Integreted Reading and Composition pada pelajaran Bahasa Indonesia. Dapat disimpulkan bahwa melalui model pembelajaran integrated reading and composition dapat meningkatkan motivasi semangat belajar siswa dalam membaca dan menulis cepat pada pelajaran Bahasa Indonesia. Kata kunci: integrated reading and composition, membaca, menulis